Impact of Openings Design Configuration on the Efficiency of Daylighting in Indoor Spaces in High-Rise Residential Buildings: Sulaymaniyah as a Case Study - Ali, Mhnaz Ismail; Ali, Amjad Muhammed (Sulaimani Journal for Engineering Sciences, 2024)
Daylighting has a crucial role in building design, influencing occupant well-being, visual comfort, energy consumption, and overall sustainability as part of the effort to establish a more comfortable indoor living environment. In the context of high-rise residential buildings, optimizing the design configuration of openings becomes particularly crucial due to unique challenges associated with verticality and climate conditions. This paper investigates the impact of opening design configuration on architectural designs. So, the research objectives are to evaluate the configuration of openings and their effects on the efficiency of daylighting in indoor spaces to make an efficient illumination level to provide a comfortable indoor living environment. The research problem arises from the lack of consideration standards that contribute to design parameters of openings and comfort illuminated levels in spaces. A hypothesis should be formed: The opening design configuration is not appropriate to provide efficient daylight levels in indoor spaces of high-residential buildings in Sulaymaniyah City in the Kurdistan Region. The results determined the impact and effects of opening formation on the efficiency of daylighting in indoor spaces, such as the size, shape, and proportion of openings in the fenestration of residential units.
Keywords: Openings Design; Daylighting; Indoor Spaces; Residential Buildings; Revit Program